Agroecosystem Management on Green Mustard Plants in Wetlands during Dry Season - Ilhamiyah Ilhamiyah; Salamiah Salamiah; Samharinto Samharinto; Hakimah Halim (Journal of Wetlands Environmental Management, 2019)
This research aimed to find a pattern of agroecosystem management that can increase arthropod diversity, production, and Return Cost Ratio (RCR) values in organic wetlands planted during the dry season.  This research was set in Randomized Block Design (RAK) with seven treatments and five repetitions, namely:  1) Intercropping  between green mustard  and basil, with chicken manure and without Bacillus thuringiensis;  2) Intercropping between green mustard and basil with water hyacinth compost, and without B. thuringiensis;  3)  intercropping between green mustard and leek, given water hyacinth compost, and without application B. thuringiensis;  4)Intercropping between green mustard  and leek, given chicken manure, and without application B. thuringiensis;  5) Intercropping between green mustard and leek, given chicken manure, and given B. thuringensis application, doubled of recommended dosage; 6) Intercropping between green mustard and leek with chicken manure, and B. thuringensis application according to recommended dosage; 7) Monoculture of green mustard without organic fertilizer and without the application B. thuringiensis.  From this research, it was concluded that the pattern of agroecosystem management of green mustard that can increase arthropod diversity in organic wetlands planted during dry season was the intercropping treatment between green mustard with basil, together with chicken manure and without B. thuringiensis. Meanwhile, the pattern of agroecosystem management of green mustard that can increase the production of green mustard and RCR value on the organic wetlands planted in the dry season was the intercropping treatment between green mustard with leek, together with chicken manure, and without B. thuringiensis.